2011
DOI: 10.4103/0019-5154.87116
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis: Zinc can be effective in treatment of vitiligo

Abstract: Vitiligo is a common depigmenting skin disorder (prevalence 0.1-2%), still represents a cause of stigmatization and quality of life impairment in a large population. Several theories on vitiligo etiopathogenesis have been suggested including in trauma, stress, and autoimmune and genetic predisposition, accumulation of toxic compounds, altered cellular environment, imbalance in the oxidant-antioxidant system, impaired melanocyte migration and/or proliferation, infection, and psychological factors. Zinc, as a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 48 publications
0
48
0
2
Order By: Relevance
“…The effectiveness of zinc treatment therapy of many skin diseases, including seborrheic dermatitis, dandruff, psoriasis, androgenic alopecia or also chronic ulcerations and viral verruca has been confirmed [17].…”
Section: Effects Of Zinc Deficiencymentioning
confidence: 94%
See 1 more Smart Citation
“…The effectiveness of zinc treatment therapy of many skin diseases, including seborrheic dermatitis, dandruff, psoriasis, androgenic alopecia or also chronic ulcerations and viral verruca has been confirmed [17].…”
Section: Effects Of Zinc Deficiencymentioning
confidence: 94%
“…The most important is cellular respiration, cellular usage of oxygen, DNA and RNA replication, maintaining the integrity of the cell membrane, and also intercepting free radicals [17].…”
Section: Zinc Interactions With Other Elementsmentioning
confidence: 99%
“…The efficacy of oral Zn supplementation has been reported in the treatment of AV [1,23,[30][31][32]. Studies have shown that oral Zn supplementation can reduce the severity of mild and moderate inflammatory AV when either administered alone or in combination with other acne treatments [30,33,34].…”
Section: Acne Vulgarismentioning
confidence: 99%
“…The efficacy of Zn sulphate has been described in CL [1,23,35,68,73,74]. A comparative clinical trial conducted by Sharquie et al compared the intralesional treatments of acute leishmaniasis with 2% Zn sulphate, 7% sodium chloride and sodium stibogluconate.…”
Section: Cutaneous Leishmaniasismentioning
confidence: 99%
“…For the first time, as a hypothesis, Bagherani and colleagues suggested that there might be association between this glycoprotein and vitiligo, which should be confirmed (Bagherani, 2011(Bagherani, , 2012aBagherani et al, 2011;Yaghoobi et al, 2011a).…”
Section: Etiology and Pathogenesis Of Vitiligomentioning
confidence: 99%